Analysis of the Role of BSI Gold Pawn and Gold Installment Products in Increasing Sharia Financial Inclusion: An SDGs Perspective - Ninda Ardiani; Lathifatul Khoirun Nisa (Research Parks Publishers, 2025)
This study was conducted to examine the role of Bank Syariah Indonesia's (BSI) Gold Pawn and Gold Installment products in increasing Islamic financial inclusion and helping achieve SDGs Goal 8 on Decent Work and Economic Growth. The study was conducted using a qualitative approach through a case study at BSI KCP Sidoarjo Cemengkalang, with data sources consisting of interviews with pawn officers, marketing, and Branch Managers, as well as secondary data such as BSI's annual report, OJK publications, SNLIK, and national media coverage. The Gold Pawn product aims to meet the short-term liquidity needs of the community, especially MSMEs, while the Gold Installment product tends to be positioned as a real asset-based investment instrument. The continuous growth of BSI's gold business reflects the strengthening credibility of Islamic financial products. Overall, both products play a role in encouraging inclusive economic growth, empowering MSMEs, and improving community welfare in a sustainable manner.